Rekonstruksi Epistemologi Ilmu Pendidikan Bahasa Arab di Era Kecerdasan Buatan: Telaah Filosofis atas Akal, Wahyu, dan Sistem Algoritmik - Muhammad Ghoniyul Fahmi; Faizurrizqi Faizurrizqi; Azzam Sidqin Qawiyya; Rohanda Rohanda; Abdul Kodir (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2026)
Abstract: This study aims to reconstruct the epistemology of knowledge in Arabic language education in the era of artificial intelligence by examining the relationship between reason, revelation, and algorithmic systems. The study employs a qualitative method based on library research, using a philosophical-epistemological approach and conceptual analysis of literature on Islamic epistemology, philosophy of science, Arabic language education, and contemporary studies on artificial intelligence. The findings indicate that the epistemology of knowledge in Arabic language education has traditionally been grounded in the integration of reason and revelation as the primary sources of knowledge, whereas artificial intelligence possesses an epistemic character that is instrumental, data-driven, and non-intentional. Therefore, artificial intelligence cannot be positioned as an autonomous source of knowledge but rather as an epistemic tool operating under the guidance of human reason and the normative values of revelation. The reconstruction of an integrative epistemology of knowledge in Arabic language education necessitates an epistemic hierarchy that positions revelation as the normative source, reason as the instrument for understanding and developing knowledge, and algorithmic systems as technological means that support the learning process. These findings contribute theoretically to strengthening the epistemological foundations of Arabic language education, ensuring its continued relevance in the face of technological advancement without losing its value orientation and meaningful purpose. Keywords: Reason, Epistemology of Knowledge, Artificial Intelligence, Arabic Language Education, Algorithmic Systems, Revelation.Abstrak: Penelitian ini bertujuan untuk merekonstruksi epistemologi ilmu dalam pendidikan bahasa Arab di era kecerdasan buatan dengan menelaah relasi antara akal, wahyu, dan sistem algoritmik. Penelitian ini menggunakan metode kualitatif berbasis studi kepustakaan (library research) dengan pendekatan filosofis-epistemologis dan analisis konseptual terhadap literatur epistemologi Islam, filsafat ilmu, pendidikan bahasa Arab, serta kajian kontemporer mengenai kecerdasan buatan. Hasil penelitian menunjukkan bahwa epistemologi ilmu dalam pendidikan bahasa Arab secara tradisional bertumpu pada integrasi akal dan wahyu sebagai sumber utama pengetahuan, sementara kecerdasan buatan memiliki karakter epistemik yang bersifat instrumental, berbasis data, dan non-intensional. Oleh karena itu, kecerdasan buatan tidak dapat diposisikan sebagai sumber pengetahuan otonom, melainkan sebagai alat bantu epistemik yang berada di bawah kendali akal dan nilai-nilai wahyu. Rekonstruksi epistemologi ilmu pendidikan bahasa Arab yang integratif menuntut adanya hierarki epistemik yang menempatkan wahyu sebagai sumber normatif, akal sebagai instrumen pemahaman dan pengembangan ilmu, serta sistem algoritmik sebagai sarana teknologis pendukung pembelajaran. Temuan ini memberikan kontribusi teoretis bagi penguatan landasan epistemologis pendidikan bahasa Arab agar tetap relevan dengan perkembangan teknologi tanpa kehilangan orientasi nilai dan makna.Kata kunci: Akal, Epistemologi Ilmu, Kecerdasan Buatan, Pendidikan Bahasa Arab, Sistem Algoritmik, Wahyu.